The Role of Mesenchymal Stem Cells in Stroke Recovery: A Regenerative Medicine Approach with Medical Rehabilitation - Deby Susanti Pada Vinski; Bruna Sinjari; Endang Ernandini; Natasha Cinta Vinski; Andi Kurniawan Nugroho (Riviera Publishing, 2025)
This study examines the role of mesenchymal stem cells (MSCs) in stroke recovery, exploring their regenerative properties and potential to enhance rehabilitation outcomes. Stroke remains a leading cause of long-term disability, with limited treatment options for functional recovery. This research investigates how MSC therapy, combined with conventional rehabilitation methods, can improve motor and cognitive function in stroke patients. Using case studies and patient care records, the study analyzes the effectiveness of MSC therapy in promoting neural repair, reducing disability levels, and improving overall quality of life. The findings suggest that MSC therapy significantly enhances functional recovery when integrated with rehabilitation, particularly when cerebrospinal fluid treatment is used before MSC administration. Imaging and biomarker analyses support these results, showing improvements in neurogenesis, synaptic plasticity, and reduced neuroinflammation. This research highlights the synergistic effects of MSC therapy and rehabilitation, presenting a promising approach to stroke recovery. The study also emphasizes the need for further research to optimize MSC-based treatments, refine delivery methods, and evaluate long-term safety and effectiveness. The implications of this study contribute to the development of integrated therapeutic strategies for stroke patients, offering a more holistic approach to recovery.